TRANSFORMASI PENDIDIKAN AGAMA HINDU DI SD NEGERI 3 KUTAMPI DI DESA KUTAMPI KECAMATAN NUSA PENIDA KABUPATEN KLUNGKUNG - Suwastawa, Kadek; I Gusti Ngurah Sudiana; I Ketut Tanu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The aim of this research is to understand: 1) The need to transform Hindu religious education atSD Negeri 3 Kutampi. 2) Forms of transformation of Hindu Religious Education at SD Negeri 3Kutampi. 3) Implications of transforming Hindu Religious Education at SD Negeri 3 Kutampi. Theresearch method used is a qualitative method. The initial informants were determined using apurposive sampling technique. The data collection techniques used were observation, interviewsand documentation. The data analysis technique is descriptive qualitative. Based on the qualitativedescriptive analysis obtained, the research results are as follows: 1) The reasons why it isnecessary to transform Hindu religious education at SD Negeri 3 Kutampi are, firstly, because thenumber of students is small. Second, the existence of Hindu religious education in this school is notyet widely known by the public. Apart from that, inadequate educational facilities are a challenge inthemselves. 2) Forms of transformation of Hindu Religious Education at SD Negeri 3 Kutampi,namely, the leadership of the Principal, facilities and infrastructure, basic legal rules, andtransformation in the curriculum field. 3) The implications of transforming Hindu ReligiousEducation at SD Negeri 3 Kutampi, namely, a better school image, increased student numbers,increased teacher and student achievement and increased student spiritual impact. The implicationsof research on the transformation of Hindu religious education at SD Negeri 3 Kutampi show thattransformation through inclusive leadership, improving infrastructure, and implementing fairpolicies can strengthen the school's image and attract more students.